Factors associated with defaulting among hypertensive patients - George, KAMBONDO; MUNODAWAFA, A.; Maxwell, MHLANGA; Augustine, NDAIMANI; Petty, MAKONI (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Objective(s): To determine factors associated with defaulting among hypertensive patientsseen in outpatient departments.Materials and Methods: An unmatched 1:1 case-control study design was used in the study.A total of 120 respondents were interviewed. Data was analysed through logistic regressionwith defaulting as the outcome.Results: Experiencing side effects caused by antihypertensive medication of drowsiness(Adjusted Odds Ratio = 8.5; 95% CI: 2, 36.2), impaired vision (AOR = 10.4; 95% CI: 3.1,34.8) and time spent at the health facility which was more that 1 to 7 hours (AOR = 9.1; 95%CI: 2.7, 30.3) were associated with defaulting. Knowledge of hypertensive retinopathy as aconsequence of uncontrolled hypertension was the only independent risk factor associated with reduced likelihood of defaulting among hypertensive patients (AOR = 0.1; 95% CI:0.03, 0.3).Conclusion: Increasing awareness of hypertensive complications may reduce defaulting.